Reparo de tendão calcanear comum de coelhos com xenoimplante de artéria carótida preservada em glicerina associado a células mononucleares da medula óssea autólogas - de Melo, Robson José Gomes; Gonçalves, Gentil Ferreira; Eurides, Duvaldo; Romagnolli, Patricia; Leme, Marshal Costa; Araújo, Eduardo José de Almeida; da Cunha Neto, Campo Amor Vieira [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
Fifteen adult rabbits were used to evaluate the repair of experimental common calcaneal tendon defects treated with glycerin-preserved canine carotid artery xenografts alone or associated with autologous mononuclear bone marrow cells (AMCs). Rabbits were submitted to daily clinical examination; implanted sites were analyzed under light microscopy within 15, 30 and 60 days of surgery. Pelvic limbs receiving xenografts associated with AMCs had better physical performance as well as higher collagen fiber, fibroblast, lymphocyte and new vessel counts at all postoperative time points considered. Glycerin-preserved canine carotid artery xenografts associated with AMCs constituted an effective method for common calcaneal tendon repair in rabbits.
Common calcaneal tendon repair with glycerin-preserved carotid artery xenografts and autologous bone marrow mononuclear cells in rabbits
Keywords: Adult stem cells; Surgery; Tendon